Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Web PhET Simulation Terhadap Hasil Belajar Matematika Peserta Didik Kelas IV SD - HAFID - TRIAWAN; Yoga Fernando Rizqi; Muhisom - -; Sowiyah - - (Didaktika Dwija Indria, 2025)
This study was motivated by the low mathematics learning outcomes of fourth grade students of SD Negeri 3 Gunung Sugih Pasar, especially on area measurement material. The purpose of this study was to determine the effect of the Problem Based Learning model assisted by PhET Simulation media on student learning outcomes. This research provides theoretical benefits in the development of problem-based learning with interactive media, as well as practical benefits as a reference for educators in choosing innovative learning strategies. The method used is quantitative with a quasi experiment design type nonequivalent control group design. The sample amounted to 54 students, consisting of experimental and control classes, with sampling techniques using non-probability sampling. The research was conducted at SDN 3 Gunung Sugih Pasar in the even semester of the 2024/2025 school year. Data collection techniques are done through pretest and postest. The results of the study based on hypothesis testing using simple linear regression showed that there was an effect of using the Problem Based Learning model assisted by PhET Simulation media on the mathematics learning outcomes of grade IV elementary school students.